The Impact of Negative Emotions on Student College Transferring Decision - Hoang Ngoc, Bui (VNU Journal of Science: Education Research; Vol 36 No 2, 2020)
Negative emotions are the result of unpleasant experiences when using a product or service. In education, the low-level of negative emotions are "early warning signals" about student confidence in a diminished university. At a higher level, negative emotions can lead to a variety of coping behaviors such as complaint, sharing a negative word-of-mouth, and switching intention. The study employed the Partial Least Square - Structural Equation Modeling to analyze the relationship between negative emotions and switching decisions in a sample of 374 students who are studying at the University of Labour and Social Affairs, Ho Chi Minh campus (ULSA2). The empirical results revealed that there is a positive impact of anger, frustration on the complaint, and negative word-of-mouth. The regret leads to switching intention. Result of the research are references to university managers in policy planning.